Tinjauan Literatur Hukum Ketenagakerjaan terhadap Perlindungan Hak Hak Dasar Pekerja Alih Daya (Outsourcing) Pasca Berlakunya Undang Undang Cipta Kerja - Mu'ammar Kadhafi; Nanda Ade Putra Rudianto; Muhamad Gilang Ardiansyah (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the transformation of legal protection for outsourcing workers following the enactment of Law Number 6 of 2023 concerning Job Creation through a normative doctrinal approach combined with a Systematic Literature Review method. The analysis focuses on the shifting structure of labor protection regarding employment security, socio economic rights, and access to industrial justice within the Indonesian outsourcing regime. Primary legal materials consist of labor legislation, government regulations, and Constitutional Court decisions, while secondary materials include scholarly journals, legal doctrines, and comparative legal studies selected through the PRISMA protocol. The findings indicate that the Job Creation regulatory framework has accelerated the transition from protective labour law toward labour market flexibility, resulting in weakened employment certainty, fragmented welfare protection, and increasingly limited access to effective legal remedies for outsourcing workers. The study further reveals that the ambiguity of legal responsibility between outsourcing vendors and user companies has intensified structural inequality within industrial relations. Consequently, reconstruction of labor law is required to restore constitutional justice, legal certainty, and substantive protection for outsourcing workers.